India : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes economic developments in India during the 1990s. Since late 1993/94, economic activity has expanded rapidly. Fiscal policy was relaxed substantially in 1993/94, a move that was only partly reversed in 1994/95. Like some other emerging markets, India experienced a surge of capital inflows, which contributed to a loosening of monetary conditions, notwithstanding efforts by the Reserve Bank to tighten monetary policy. With increased confidence and greater access to foreign financing, private investment has increased sharply. On the structural side, the authorities have continued to press ahead with reforms in a number of areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet